Human dramas and Dilemmas at work: New-gen cases in organisational behaviour - Manimala, Mathew J.; Venkateswaran, Vijaya; Chakravarti, Ajit (London Routledge, 2025)
This book presents 120 real-life case-studies collected from indigenous as well as multinational organizations operating in India in 18 different industry sectors. These cases provide the readers with insights into 'the good, the bad and the ugly' facets of the corporate lives of new-gen professionals in the last two decades.Based on real-life work experiences of corporate executives in India, these cases address a variety of the multitude of issues being faced by the professionals and their behavioural implications at the workplace.